2020
DOI: 10.1088/2633-1357/abcd28
|View full text |Cite
|
Sign up to set email alerts
|

Ku-Band scintillation over Akure, Nigeria

Abstract: Relationship between scintillation intensity (σ χ ) and peak-to-peak amplitude (χ pp) is important for mitigating scintillation effects on any communication link. This study employs linear, logarithmic and polynomial functions for fitting σ χ and χ pp in order to determine the best model for describing the variation of the former with the latter. It also exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…All variations in signal due to scintillation usually last for a period of few seconds irrespective of the underlying cause. This forms the basis for differentiating scintillation from slow-fading rain attenuation events which are known to last for periods of several minutes (Ashidi 2020). Furthermore, unlike rain fading, scintillation is not a lossy process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All variations in signal due to scintillation usually last for a period of few seconds irrespective of the underlying cause. This forms the basis for differentiating scintillation from slow-fading rain attenuation events which are known to last for periods of several minutes (Ashidi 2020). Furthermore, unlike rain fading, scintillation is not a lossy process.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few works on tropospheric amplitude scintillation have been reported from Nigeria due to dearth of data, these include but not limited to-characterization of Ku-band amplitude scintillation on Earth-space path over Published in partnership with CECCR at King Abdulaziz University Akure, SW Nigeria (Ashidi 2020;Ashidi et al 2017Ashidi et al , 2020Ashidi et al , 2021, experimental analysis and comparison of tropospheric scintillation prediction models in tropical Nigeria (Ojo et al 2018), analysis and comparison of tropospheric scintillation prediction models at Covenant University (Akinwumi et al 2018), and prediction of tropospheric scintillation over some selected locations in Nigeria (Adebo and Akindugbagbe 2019). Locally, no study has been reported on the concurrent evaluation of rain attenuation with amplitude scintillation.…”
Section: Introductionmentioning
confidence: 99%